2018
DOI: 10.1002/ajmg.a.61002
|View full text |Cite
|
Sign up to set email alerts
|

Association of low‐frequency genetic variants in regulatory regions with nonsyndromic orofacial clefts

Abstract: Genome-wide scans have shown that common risk alleles for orofacial clefts (OFC) tend to be located in noncoding regulatory elements and cumulatively explain only part of the heritability of OFCs. Low-frequency variants may account for some of the "missing" heritability. Therefore, we scanned low-frequency variants located within putative craniofacial enhancers to identify novel OFC risk variants and implicate new regulatory elements in OFC pathogenesis. Analyses were performed in a multiethnic sample of 1,995… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Prescott et al used a collection of craniofacial enhancers identified and characterized by the Visel Spoke in a study of regulatory divergence of neural crest enhancers between chimpanzees and humans (Prescott et al, 2015). Shaffer et al used enhancer data generated by this Spoke to identify a significant association between cleft palate and a branchial arch enhancer at the FOXP1 locus (Shaffer et al, 2019). Finally, Carlson et al used data from this Spoke to examine the regulatory basis of phenotypic modifiers of non-syndromic cleft lip with or without cleft palate (Carlson et al, 2017).…”
Section: Facebase 2 Spoke Projectsmentioning
confidence: 99%
“…Prescott et al used a collection of craniofacial enhancers identified and characterized by the Visel Spoke in a study of regulatory divergence of neural crest enhancers between chimpanzees and humans (Prescott et al, 2015). Shaffer et al used enhancer data generated by this Spoke to identify a significant association between cleft palate and a branchial arch enhancer at the FOXP1 locus (Shaffer et al, 2019). Finally, Carlson et al used data from this Spoke to examine the regulatory basis of phenotypic modifiers of non-syndromic cleft lip with or without cleft palate (Carlson et al, 2017).…”
Section: Facebase 2 Spoke Projectsmentioning
confidence: 99%
“…Interestingly, this association would have been missed if only the coding parts of the genes had been considered. Another example is the study performed by Shaffer et al (Shaffer et al 2019) where they looked for an accumulation of rare variants in enhancers in orofacial clefts phenotype using CMC (Li and Leal 2008) and SKAT (Wu et al 2011) association tests. They grouped rare variants by enhancers that were defined using different sources including the VISTA database (Visel et al 2007), results from ChIP-Seq studies and a literature search, and found an association with an enhancer near FOXP1.…”
Section: Using Functional Annotationsmentioning
confidence: 99%
“…Significantly, Tgfbr1 and Tgfbr2 mutant mice also exhibit cleft palate, suggesting that Tgf-β signaling pathway is crucial in regulating palatogenesis (Han et al 2014; Iwata et al 2014). Recent studies on patients with nonsyndromic orofacial clefts have revealed that differential DNA methylation, epigenetic regulator mutations, and low-frequency genetic variants in noncoding regions may contribute to cleft palate (Alvizi et al 2017; Shaffer et al 2019). It is crucial to develop relevant animal models to test how epigenetic factors may control palate development.…”
Section: Molecular and Cellular Regulatory Mechanisms Of Soft Palate Developmentmentioning
confidence: 99%